The separate and combined effects of recasts and textual enhancement as two focus on form techniques on L2 development. (April 2020) - Rassaei, Ehsan
Abstract: The present study examined the effects of recasts and textual enhancement (TE), separately and in tandem, on EFL learners' accuracy in using English articles. To this end, four intact EFL classes in Iran were designated as three experimental conditions as well as a control group. The participants of the three experimental groups received recasts, TE, or the combination of recasts and TE during four treatment sessions. The control condition received neither TE nor recasts during the treatment sessions. Two testing instruments were administered on two occasions, as pretest and post-test to examine the development of the target forms as a result of the treatment conditions. Stimulated recall interviews were also held with the participants of the recasts and recasts combined with TE conditions following the post-test to examine the learners' perceptions of the recasts they received during the recasts sessions. The results provided evidence for the benefits of recasts alone and also the superiority of recasts plus TE condition over recasts alone for L2 development. Meanwhile, the results did not provide robust evidence that TE alone promotes L2 development. Moreover, the results of the stimulated recall interviews indicated that the learners had more accurate perceptions of recasts when recasts were accompanied by TE.